Semiempirical QM/MM calculations reveal a step-wise proton transfer and an unusual thiolate pocket in the mechanism of the unique arylpropionate racemase AMDase G74C. Issue 13 (11th March 2016) - Busch, F.; Enoki, J.; Hülsemann, N.; Miyamoto, K.; Bocola, M.; Kourist, R.
Abstract : Semiempirical calculations on the mechanism of the arylpropionate racemase AMDase G74C reveal a step-wise mechanism involving a planar-enedionate intermediate. Abstract : The mechanism of the unique arylpropionate racemase AMDase G74C was investigated by a QM/MM approach. Molecular dynamics simulations showed that the mechanism is initiated by a deprotonation of the catalytic cysteine. The simulations revealed two thiolate pockets. While the first plays a role in the natural decarboxylative activity of AMDase, the second stabilizes the artificially introduced thiolate group of C74. The presence of the two structural motifs is a prerequisite for the promiscuous racemization reaction of AMDase G74C. QM/MM simulations show that the deprotonation and reprotonation proceed in a stepwise fashion, in which a planar enedionate intermediate is stabilized by a delocalized π-electron system on a vinylic or aromatic substituent of the substrate. The artificial racemase is thus a typical case of substrate-assisted catalysis.